CONDITION OF THE MICROCIRCULATION IN ADOLESCENTS WITH OBESITY AND CONCOMITANT INVOLVEMENT OF THE PANCREAS: MODERN LOOK AT THE PROBLEM AND OUR OWN CLINICAL SUPERVISION - Лембрик, І.С.; Тимощук, О.В.; Кочерга, З.Р. (World of Medicine and Biology, 2018)
In view of worldwide burden of obesity, triggers leading to it in children and adolescents have to be urgently identified. Publications of recent years reveal the important pathogenetic role of the pancreas in regulation and activity of the microcirculation, at the level of target organs due to future appearance of abdominal ischemic syndrome, and in general, systemic atherosclerosis. Microcirculation (in particular, arterioles, capillaries and venules) is conceivably a key compartment or “special mirror” determining the situation in a whole organism. It is confirmed, that indirect methods of investigation of microcirculation are not known since nowadays. Objectives of the study: to improve condition of the microcirculation in adolescents with alimentary-constitutional obesity with involvement of the pancreas. Materials and methods of investigation. The article presents data on the state of microcirculation in 120 adolescents with primary obesity combined with functional pancreatic disorder and without it, as well as in 30 adolescent control groups. All children were examined in accordance with modern diagnostic and treatment protocols. During the work, the basic principles of bioethics were adhered to: informed consent was received from one parent (mother) for the participation of the child in the study, adhered to the basic principles of the Helsinki Declaration (1975 with its subsequent revision in 2000). During the conduction of scientific research, no biological experiment was conducted involving vertebrate animals. The min principles of bioethics were followed. Results of the investigation. According to our data, alimentary-constitutional obesity in adolescence is accompanied by pancreatic lesion more frequently (54.2% and 45.8%, p> 0.05). The combined pathology of the digestive system predominantly affects boys (61.5% and 38.5%, p